Preferensi dan Ambang Deteksi Rasa Manis dan Pahit: Pendekatan Multikultural dan Gender - Uswatun Hasanah; Dede Robiatul Adawiyah; Budi Nurtama (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
Indonesia is a multicultural country and each ethnic group has different eating habits and basic taste preference of food. Gender is also known to have different preference in basic taste. The objective of this research was to study the effect of culture and gender on preference and detection threshold of sweetness and bitterness in Minang (West Sumatra), Javanese (Central Java) and Nusa Tenggara ethnic groups. The numbers of panelists were 90 first year undergraduate students in Bogor Agricultural University recruited from regional student organizations. The preference test was rankrating hedonic test in tea for sweetness and coffee for bitterness. Detection threshold experiment was conducted using 3AFC (3-alternative forced choice) method in standard solutions of sucrose and caffeine. Different culture of origin significantly affects preferences of sweetness in tea beverage. Panelists from Minang prefer higher level of sweetness compared to Javanese and Nusa Tenggara ethnic group. However, cultural differences did not affect preference to bitterness of coffee or bitterness. Overall, Indonesians tend to prefer tea beverage with high level of sweetness, and coffee with very low level of bitterness. Gender did not affect significantly the preferences of sweetness and bitterness, but detection threshold of female panelists was lower than that of male panelists. Women were more sensitive than man to detect sweetness and bitterness.